Synovial inflammation assessed by ultrasonography correlates with MRI-proven osteitis in patients with rheumatoid arthritis. (22nd March 2014) - Kawashiri, Shin-ya; Suzuki, Takahisa; Nakashima, Yoshikazu; Horai, Yoshiro; Okada, Akitomo; Nishino, Ayako; Iwamoto, Naoki; Ichinose, Kunihiro; Arima, Kazuhiko; Tamai, Mami; Nakamura, Hideki; Origuchi, Tomoki; et al.
Abstract : Objective. The aim of this study was to explore whether assessment of synovial inflammation by ultrasonography correlates with MRI-proven osteitis in patients with RA. Methods. Thirty RA patients who fulfilled 2010 RA classification criteria and were naive to DMARDs, including biologics and glucocorticoids, were consecutively enrolled in this study. Grey scale (GS) and power Doppler (PD) images of articular synovitis and bone erosion in both wrist and MCP joints were evaluated by the method proposed by the European League Against Rheumatism. MRI-proven osteitis of the identical sites was also evaluated within 3 days using the RA MRI scoring system (RAMRIS). The Cochran–Armitage test and Spearman's correlation coefficient were used to investigate the correlation of each US finding with MRI-proven osteitis. Results. MRI-proven osteitis was found in 8.3% of MCP joints and 48.3% of wrist joints. Its prevalence was increased in the joints where the GS or PD grade of articular synovitis was 2 or 3. In addition, MRI-proven osteitis was found preferentially in the joints positive for bone erosion on US. A clear correlation was demonstrated between the GS or PD grade of articular synovitis or the presence of US bone erosion and RAMRIS osteitis score in both MCP joints and wrist joints. Conclusion. Our data indicate that joint injury assessed by US correlates with MRI-proven osteitis in patients with RA.